Experimental Study on Bendable Concrete using Super Plasticizer and Recron 3s Fibre - Sahil, Pathan; Dattatray, Ghodekar; Karishma, Rode; Kalyani, Kharat; Somawanshi, Shivsiddha (International Journal of Scientific Research in Civil Engineering, 2020)
Concrete is one of the most extensively used construction material all over the world. Many scientists and researchers are in quest for developing alternate construction material that are environment friendly and contribute towards sustainable development. Huge amount of rubber tire waste is being generated day by day which creates the disposal problems and has many environmental issues as this scrapped rubber waste is an elastic material having less specific gravity, energy absorbent material can be used as a replacement material for obtaining lightweight concrete. The scrapped rubber can not be discharge of easily in the environment as its decomposition takes much time and also produces environmental pollution .In such a case the reuse of rubber would be a better choice. In order to reuse rubber wastes, it is added to concrete to enhance the properties of concrete. The objective of this study is to test the properties of concrete by replacing the waste rubber chips partially to the coarse aggregate in concrete with different percentage as 10%, 20% and 30% on volume basis. By literature review it is observed that it helps to reduce cracks and also helps to increase the durability and ductility of concrete. Because of rubber compressive strength of concrete decreases. So, to increase the compressive strength we are adding glass fiber to the weight of cement in concrete at percentage 0.5%, 1% and 1.5%. The glass fiber having high tensile strength, good thermal conductivity and also good chemical resistance.
Keywords: Reinforced Concrete; Workability; Compressive Strength; Tensile Strength; Bond Strength